Effects of Several Botanical Insecticides Applied in Different Periods to Control Aphids (Macrosiphoniella sanborni Gillete) on Chrysanthemum - Indijarto Budi Rahardjo; Dedi Hutapea; Budi Marwoto; Kurniawan Budiarto (AGRIVITA, Journal of Agricultural Science, 2021)
Pest management in the agricultural process has faced worldwide economic and ecological issues related to chemicals usage. Botanical insecticides have long been considered promising alternatives to control pests because botanicals reputedly pose a minor threat to the environment and human health. Some studies have evaluated several botanical insecticides to control aphids in chrysanthemum. The research was conducted under plastic house conditions at the Indonesian Ornamental Crops Research Institute from January to December 2018. Leaf extract of T. sinensis, T. diversifolia and A. indica at the concentration of 3 and 3.5 g/l, processed oil of C. nardus at the concentration of 2.5 and 5 g/l and synthetic insecticide Imidacloprid 1 g/l were sprayed in the morning or late afternoon. The results showed that aphid attacks severity and percentage of attacked plants were lower when the insecticides were applied in the late afternoon. Slightly softer than synthetic chemicals, the leaf extract of T. sinensis at 3 g/l suppressed the aphid development more effective for about 55.93% than other botanicals treatments. On reproductive properties, the leaf extract of T. sinensis at 3 and 3 g/l and T. diversifolia at 3 g/l induced a higher percentage of open flower for more than 65% than synthetic insecticides, Imidacloprid.